Effect of pulverisation on sulfide and tin antimonide anodes for sodium-ion batteries - Priyanka, P.; Nalini, B.; Soundarya, G. G.; Christopher Selvin, P.; Dutta, Dimple P. (Frontiers in Energy Research, 2023)
Metal sulfides and alloy anodes are good choice for Sodium-Ion Batteries (SIBs) since it has many benefitting advantages such as higher specific capacity, good cycling stability and higher rate capability. Tin antimony (Sn2Sb3) as an anode exhibits remarkable theoretical capacity of 753 mAhg-1 that has not been realized so far for reaching the theoretical capacity, pulverization of sulfide based material (Copper sulfide (CuS)) along-with tin antimonide would be a better option for obtaining higher performance anode for SIBs. Hence, an attempt is made to study the pulverisation effects of these two materials when employed as an anode for SIBs. The pulverised compound CuS: Sn2Sb3 delivers an initial discharge capacity of 659 mAhg-1 at 0.1 Ag-1 vs. Na/Na+ with high stability retaining upto 100% efficiency over 100 cycles. The present work highlights the structural changes upon pulverisation and its impact on delivering higher capacity.